A Literature Review on Live Migration in Container-Based Distributed Systems - Barroso, João Pedro Resende; Manacero, Aleardo; Lobato, Renata Spolon; Spolon, Roberta (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2025)
Task schedulers are a cornerstone of high-performance distributed computing systems, efficiently distributing workloads across multiple nodes to optimize resource utilization and enhance application performance. By balancing computational tasks, they ensure scalability, minimize latency, and maintain system reliability. Live container migration is an emerging technology in the area of task schedulers; it involves making the task of rescheduling containers as fast as possible, thereby reducing the idle time of the system. This article reviews the most relevant works in the area of live migration in container-based distributed systems, identifying the most significant innovations on the subject.